Pregnancy outcomes between pregnant systemic lupus erythematosus patients with clinical remission and those with low disease activity: A comparative study - Worawit Louthrenoo; Thananant Trongkamolthum; Nuntana Kasitanon; Antika Wongthanee (Archives of Rheumatology, 2022)
Objectives: This study aims to compare pregnancy outcomes between systemic lupus erythematosus (SLE) patients who attained clinical remission based on the Definition of Remission in SLE (DORIS) and those with lupus low disease activity based on Low Lupus Disease Activity State (LLDAS). Patients and methods: Between January 1993 and June 2017, a total of 90 pregnancies (one twin pregnancy) from 77 patients (mean age: 26.9±4.8 years; range, 17.9 to 37.3 years) were included in the study. The clinical remission and the LLDAS groups were modified into modified clinical remission and LLDAS groups, respectively by omitting Physician Global Assessment (PGA). The clinical SLE disease activity index (cSLEDAI) score was used for LLDAS. Results: Pregnancies in 49 patients occurred, when they were in modified clinical remission and in 57 in modified LLDAS. There was no significant difference in demographic characteristics, disease activity, or medication received at conception between the two groups. Pregnancy outcomes were similar between the modified clinical remission and the modified LLDAS groups in terms of successful pregnancy (83.67% vs. 84.21%), full-term births (38.78% vs. 38.60%), fetal losses (16.33% vs. 15.79%), spontaneous abortions (14.29% vs. 14.04%), small for gestational age infants (18.37% vs. 19.30%), low birth weight infants (42.86% vs. 40.35%), maternal complications (46.94% vs. 49.12%), and maternal flares (36.73% vs. 40.35%). The agreement of pregnancy outcomes was very high between the two groups (91.11% agreement). Conclusion: Pregnancy outcomes in SLE patients who achieved modified clinical remission and modified LLDAS were comparable